Nicotinaldehyde [2,8-bis(trifluoromethyl)quinolin-4-yl]hydrazone monohydrate - H. C. Devarajegowda; Suresh Babu Vepuri; M. VinduVahini; H. D. Kavitha; H. K. Arunkashi (Acta Crystallographica Section E, 2010)
In the title compound, C17H10F6N4·H2O, the pyridine ring is not coplanar with the quinoline ring system; the dihedral angle between the two planes is 21.3 (1)°. One of the trifluoromethyl group is disordered over two orientations with occupancies of 0.70 (1) and 0.30 (1). The water molecule is disordered over two positions with occupancies of 0.76 (1) and 0.24 (1). In the crystal, the water molecule is linked to the main molecule via N—H...O and C—H...O hydrogen bonds, and inversion-related pairs are linked via O—H...N hydrogen bonds. In addition, a weak π–π interaction is observed between the pyridine ring and the pyridine ring of the quinoline unit, with a centroid–centroid distance of 3.650 (2) Å.